Therapeutic Approaches for Dominant Muscle Diseases: Highlight on Myotonic Dystrophy - F. Klein, A.; Dastidar, S.; Furling, D.; K. Chuah, M. (Current Gene Therapy, 2015)
Myotonic Dystrophy (DM), one of the most common neuromuscular disorders in adults, comprises two genetically distinct forms triggered by unstable expanded repeats in non-coding regions. The most common DM1 is caused by expanded CTG repeats in the 3’UTR of the DMPK gene, whereas DM2 is due to large expanded CCTG repeats in the first intron of the CNBP gene. Both mutations induce a pathogenic RNA gain-of-function mechanism. Mutant RNAs containing CUG or CCUG expanded repeats, which are retained in the nuclei as aggregates alter activities of alternative splicing regulators such as MBNL proteins and CELF1. As a consequence, alternative splicing misregulations of several pre-mRNAs are associated with DM clinical symptoms. Currently, there is no available cure for this dominant neuromuscular disease. Nevertheless, promising therapeutic strategies have been developed in the last decade. Preclinical progress in DM research prompted the first DM1 clinical trial based on antisense oligonucleotides promoting a RNase-H-mediated degradation of the expanded CUG transcripts. The ongoing Phase 1/2a clinical trial will hopefully give further insights into the quest to find a bona fide cure for DM1. In this review, we will provide an overview of the different strategies that were developed to neutralize the RNA toxicity in DM1. Different approaches including antisense oligonucleotide technologies, gene therapies or small molecules have been tested and validated in cellular and animal models. Remaining challenges and additional avenues to explore will be discussed.
Keywords: DMPK